(untitled) (Journal of Applied Oral Science, 2021)
Implant surface decontamination is a challenging procedure for therapy of peri-implant disease. Objective: This study aimed to compare the effectiveness of decontamination on oral biofilm-contaminated titanium surfaces in Er:YAG laser, Er, Cr:YSGG laser, and plastic curette. Methodology: For oral biofilms formation, six participants wore an acrylic splint with eight titanium discs in the maxillary arch for 72 hours. A total of 48 contaminated discs were distributed among four groups: untreated control; decontamination with plastic curettes; Er, Cr:YSGG laser; and Er:YAG laser irradiation. Complete plaque removal was estimated using naked-eye and the time taken was recorded; the residual plaque area was measured and the morphological alteration of the specimen surface was observed by scanning electron microscopy. The total bacterial load and the viability of adherent bacteria were quantified by live or dead cell labeling with fluorescence microscopy. Results: The mean treatment time significantly decreased based on the treatment used in the following order: Er:YAG, Er, Cr:YSGG laser, and plastic curettes (234.9±25.4 sec, 156.1±12.7 sec, and 126.4±18.6 sec, P=0.000). The mean RPA in the Er, Cr:YSGG laser group (7.0±2.5%) was lower than Er:YAG and plastic curettes groups (10.3±2.4%, 12.3±3.6%, p=0.023). The viable bacteria on the titanium surface after Er, Cr:YSGG laser irradiation was significantly lower compared to the decontamination with plastic curette (P=0.05) but it was not significantly different from the Er:YAG laser irradiation. Conclusion: We found that Er:YAG laser and Er, Cr:YSGG laser irradiation were effective methods for decontaminations without surface alterations.